An extensive analysis and conduct comparative based on statistical attach of LSB substitution and LSB matching - Mahdi Hashim, Mohammed; Shafry Mohd Rahim, Mohd; Abass Johi, Fadil; Sabah Taha, Mustafa; A. Al-Wan, Ali; Nur Amir Sjarif, Nilam (International Journal of Engineering and Technology, 2018)
Steganography and steganalysis are the two diverse sides of the same coin, as steganalysis is a countermeasure to steganography. The major function of steganalysis is to differentiate between actual media and suspected media that contains concealed messages. Carrying out this task can be difficult for new adaptive steganography, because modifications made as a result of concealed messages is very minimal. De-spite the availability of so many techniques in recent times, some of the oldest and most commonly used technique in the last years is the LSB substitution and matching techniques. The statistical steganalysis in LSB substitution and LSB matching approach for the digital imag-es is being analyzed and discussed extensively in this paper. The major contribution of the paper is the evaluation of methods, by means of analyzing challenges and comparing approved studies, with the intention of unveiling novel directions which have the potentials of provid-ing improved and effective steganalysis approach.Â